Wurtzite CuGaS2 with an in-situ-formed CuO layer photocatalyzes CO2 conversion to ethylene with high selectivity - Chakraborty, Subhajit; Das, Risov; Riyaz, Mohd; Das, Kousik; Singh, Ashutosh Kumar; Bagchi, Debabrata; Vinod, Chathakudath P.; Peter, Sebastian C. (Angewandte chemie-international edition, 2023)
We present surface reconstruction-induced C-C coupling whereby CO2 is converted into ethylene. The wurtzite phase of CuGaS2. undergoes in situ surface reconstruction, leading to the formation of a thin CuO layer over the pristine catalyst, which facilitates selective conversion of CO2 to ethylene (C2H4). Upon illumination, the catalyst efficiently converts CO2 to C2H4 with 75.1 % selectivity (92.7 % selectivity in terms of R-electron) and a 20.6 mu mol g(-1) h(-1) evolution rate. Subsequent spectroscopic and microscopic studies supported by theoretical analysis revealed operando-generated Cu2+, with the assistance of existing Cu+, functioning as an anchor for the generated *CO and thereby facilitating C-C coupling. This study demonstrates strain-induced in situ surface reconstruction leading to heterojunction formation, which finetunes the oxidation state of Cu and modulates the CO2 reduction reaction pathway to selective formation of ethylene.
Keywords: C-C coupling; charge polarization; CO2 reduction; Photocatalysis

Dopant and exfoliation induced simultaneous modification of charge density and C―C coupling sites for efficient CO2 photoreduction to ethylene - Das, Kousik; Chakraborty, Subhajit; Kediya, Siddhi; Singh, Ashutosh Kumar; Das, Risov; Mondal, Soumi; Riyaz, Mohd; Goud, Devender; Dutta, Nilutpal; Vinod, Chathakudath P.; Peter, Sebastian C. (Angewandte Chemie-International Edition, 2025)
The photochemical conversion of CO2 into C2+ products has emerged as an attractive method for synthesizing valuable chemicals and fuels using abundant solar energy. However, the challenge lies in enhancing the efficiency and selectivity of C2+ product formation. In this study, we employed a heteroatom doping strategy to optimize the photocatalytic parameters and achieve excellent efficiency and selectivity in the photocatalytic CO2 reduction to C2+ product formation. Our experimental analysis revealed that the local electronic structure of the catalyst, modified by In-doping, enables enhanced efficiency. Additionally, the incorporation of Cu facilitates the coupling of C1 intermediates, resulting in excellent selectivity towards C2+ products. The CO2 reduction performance is further enhanced through exfoliation, which increases the exposure of active sites and extends the charge carrier lifetime by reducing the charge diffusion length. We report that the rate of formation of C2H4 reached 54.3 mu molh(-1)g(-1) with an outstanding selectivity of 91% over the exfoliated CuIn-doped AgBiP2S6 catalyst. By elucidating the role of heteroatom doping and exfoliation in enhancing both the efficiency and selectivity of C2+ product formation, our study contributes to advancing the development of sustainable and efficient photocatalytic CO2 conversion technologies.
Keywords: C & horbar; C coupling; CO2 reduction; Doping; Exfoliation; Photocatalysis